HPat a decapping activator interacting with the miRNA effector complex. - Elisabeth Barišić-Jäger; Izabela Kręcioch; Stefanie Hosiner; Sanja Antic; Silke Dorner (PLoS ONE, 2013)
Animal miRNAs commonly mediate mRNA degradation and/or translational repression by binding to their target mRNAs. Key factors for miRNA-mediated mRNA degradation are the components of the miRNA effector complex (AGO1 and GW182) and the general mRNA degradation machinery (deadenylation and decapping enzymes). The CCR4-NOT1 complex required for the deadenylation of target mRNAs is directly recruited to the miRNA effector complex. However, it is unclear whether the following decapping step is only a consequence of deadenylation occurring independent of the miRNA effector complex or e.g. decapping activators can get recruited to the miRNA effector complex. In this study we performed split-affinity purifications in Drosophila cells and provide evidence for the interaction of the decapping activator HPat with the miRNA effector complex. Furthermore, in knockdown analysis of various mRNA degradation factors we demonstrate the importance of NOT1 for this interaction. This suggests that deadenylation and/or the recruitment of NOT1 protein precedes the association of HPat with the miRNA effector complex. Since HPat couples deadenylation and decapping, the recruitment of HPat to the miRNA effector complex provides a mechanism to commit the mRNA target for degradation.